Algorithms for coherent diversity combining of M-ary orthogonal signals. - Thompson, J.S (IEEE Journal on selected areas in communications)
This paper discusses the use of coherent demodulation for antenna array receivers employing direct sequence spread spectrum techniques and M-ary orthogonal modulation. Three different approaches are discussed. The first is a conventional receiver using training sequences and decision feedback for channel estimation. The other two techniques employ decisions from a simple noncoherent combining (O) receiver to circumvent the need for training sequences. The bit error ratio (BER) performance of coherent M-ary orthogonal modulation is derived. Some qualitative analysis is also presented for the algorithms, and simulation results are used to compare their performance in different scenarios